The happiness of a dog with a ball in its mouth - Handy, Bruce (Enchanted Lion Books, 2021)
"Starting from the happiness of waking up into a brand-new day, the picture book goes on to explore the kinds of relationships and contrasts that play out between our feelings and experiences every single day. Whether it's the nervousness of a beginning paired with the happiness of a middle; the indignity of a cut against the happiness of a scab; the boredom of nothing to do contrasted with the happiness of nothing to do; or the divide of mine against the happiness of our, these pages challenge the reader to think about daily activities and experiences and the feelings they conjure. The Happiness of a Dog with a Ball in Its Mouth is a gentle, fun, and philosophical read."--